Răspunsuri

2014-04-07T01:39:38+03:00
11 a) x+3/12  x/12-3  x/9⇒x∈{1,3,9}
b)2x+1/15  2x/15-1  2x/14  x/7⇒ x∈{1,7}
c)2x-1/27  2x/27+1  2x/28  x/14⇒x∈{1,2,7,14}
d)x-5/6  x/6+5    x/11⇒ x∈{1,11}

12 a) x+1/x+6  x+1/x+1⇒    x+1/x+6-x-1    x+1/5 ⇒x+1∈{1,5}  x+1=1  x=1-1=0    x+1=5  x=4
b)x+2/2x+29 
x+2/x+2     x+2/2(x+2)  x+2/2x+4      x+2/2x+29-2x-4  x+2/25⇒ x+2∈{1,5,25}
x+2=1  x=1-2  x=-1∉ N
x+2=5  x=5-2  x=3
x+2=25  x=25-2  x=23

c)2x-1/4x+19
2x-1/2x-1  2x-1/2(2x-1)  2x-1/4x-2    2x-1/4x+19-4x+2  2x-1/21 ⇒2x-1∈{1,3,7,21}
2x-1=1  2x=1+1  2x=2  x=1
2x-1=3  2x=3+1  2x=4  x=2
2x-1=7  2x=7+1  2x=8  x=4
2x-1=21  2x=21+1  2x=22 x=11

d)2x+1/7x+23  2x+1/2(7x+23)  2x+1/14x+26
2x+1/2x+1    2x+1/7(2x+1)  2x+1/14x+7    2x+1/14x+26-14x-7  2x+1/19⇒ 2x+1∈{1,19}
2x+1=1  2x=1-1  2x=0  x=0
2x+1=19  2x=19-1  2x=18  x=9

e)2x+5/7x+29  2x+5/2(7x+29)  2x+5/14x+58
2x+5/2x+5  2x+5/7(2x+5)  2x+5/14x+35      2x+5/14x+58-14x-35  2x+5/23⇒ 2x+5∈{1,23}
2x+5=1  2x=1-5  2x=-4  x=-2
2x+5=23  2x=23-5  2x=18  x=9


13 a) 3x+11=4x+15  3x-4x=15-11  -x=4  x=-4
a=3x+11 ⇔a=3*(-4)+11=-12+11=-1
b=4x+15 ⇔b=4*(-4)+15=-16+15=-1
a=-1  b=-1⇒  (a,b)=-1  [a si b sunt prime intre ele]

b)6x+13=4x+9    6x-4x=9-13    2x=-4  x=-2
a=6x+13 ⇔a=6*(-2)+13=-12+13=1
b=4x+9  ⇔b=4*(-2)+9=-8+9=1
a=1    b=1 ⇒(a,b)=1